Krasnyi kvadrat . Krasnyi kvadrat . Red Square Box . Красный квадрат - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. On the process of creating new states within Russia; declaration of the Ural Republic; the problem of limiting the freedom of press; discussion of the problem of censorship in press; on the intelligence service in Russia; Featured in the program: Drachevskii, Leonid (Head of the Russian Foreign Ministry's Directorate on the Commonwealth of Independent States) О процессе образования новых государств внутри России; провозглашение Уральской республики; обсуждение проблемы цензуры в прессе; о службе внешней разведки в России. В программе участвуют: Драчевский, Леонид (Начальник Управления МИД России по делам СНГ)